Evaluating Computer Programs. (Exceptional Children, 1982)
The article reports on the publication of the "Guidelines for Evaluating Computerized Instructional Materials" by the National Council of Teachers of Mathematics. The manual is a practical resource used for instructional purposes by persons involved with the selection or creation of computer programs. The manual can be ordered from the National Council of Teachers of Mathematics in Reston, Virginia.